2021
DOI: 10.3390/pharmaceutics13091333
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Interaction and Killing-Kinetics of Amphotericin B Combined with Anidulafungin or Caspofungin against Candida auris

Abstract: Treatment of invasive infections caused by Candida auris is challenging due to the limited therapeutic options. The combination of antifungal drugs may be an interesting and feasible approach to be investigated. The aim of this study was to examine the in vitro activity of amphotericin B in combination with anidulafungin or caspofungin against C. auris. In vitro static time–kill curve experiments were conducted for 48 h with different combinations of amphotericin B with anidulafungin or caspofungin against six… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 37 publications
1
16
0
1
Order By: Relevance
“… Drug Antifungal drug FICI Isolate a Ref. Antifungal drug Micafungin Voriconazole 0.15–0.5 10/10 56 Anidulafungin Isavuconazole 0.25–0.38 11/36 38 Voriconazole 0.25–0.38 5/36 38 Amphotericin B Caspofungin ND b 6/6 100 Anidulafungin ND 6/6 100 Non-antifungal drug Sulfamethoxazole Fluconazole 0.156 1/1 101 Voriconazole 0.09–0.5 3/8 101 Itraconazole 0.186–0.373 3/4 101 Lopinavir Itraconazole 0.04–0.09 10/10 58 Voriconazole 0.19–0.31 6/10 58 Fluconazole 0.13–0.31 3/10 58 Aprepitant Itraconazole 0.14–0.31 8/10 102 Pitavastatin Fluconazole 0.25–0.5 5/5 103 Ospemifene Itraconazole 0.14–0.27 5/5 104 …”
Section: Synergistic Drug Combinations To Treat C Aurismentioning
confidence: 99%
See 2 more Smart Citations
“… Drug Antifungal drug FICI Isolate a Ref. Antifungal drug Micafungin Voriconazole 0.15–0.5 10/10 56 Anidulafungin Isavuconazole 0.25–0.38 11/36 38 Voriconazole 0.25–0.38 5/36 38 Amphotericin B Caspofungin ND b 6/6 100 Anidulafungin ND 6/6 100 Non-antifungal drug Sulfamethoxazole Fluconazole 0.156 1/1 101 Voriconazole 0.09–0.5 3/8 101 Itraconazole 0.186–0.373 3/4 101 Lopinavir Itraconazole 0.04–0.09 10/10 58 Voriconazole 0.19–0.31 6/10 58 Fluconazole 0.13–0.31 3/10 58 Aprepitant Itraconazole 0.14–0.31 8/10 102 Pitavastatin Fluconazole 0.25–0.5 5/5 103 Ospemifene Itraconazole 0.14–0.27 5/5 104 …”
Section: Synergistic Drug Combinations To Treat C Aurismentioning
confidence: 99%
“…In a time–kill curve assay against six C. auris isolates, monotherapy with echinocandins (anidulafungin and caspofungin) was ineffective, while high concentrations of amphotericin B (≥1 μg/mL) only showed fungistatic activity 100 . When used in combination, higher fungal killing activity was observed 100 . Lower doses of amphotericin B (0.5 mg/L) and anidulafungin or caspofungin (2 mg/L) achieved rapid synergism with potent fungicidal activity 100 .…”
Section: Synergistic Drug Combinations To Treat C Aurismentioning
confidence: 99%
See 1 more Smart Citation
“…Thus far, nine studies have examined antifungal drug combinations against C. auris. The majority of these studies focussed on combinations of azoles with echinocandins (20,23,24,38), while a smaller number have evaluated polyene-echinocandin interactions (21,22) or combinations with 5-flucytosine (25)(26)(27). These studies reported mainly synergistic (including partial synergy) or indifferent interactions, with inter-strain variability observed for some combinations.…”
Section: Auris Currently Appears Susceptible To the Active Version Of...mentioning
confidence: 99%
“…There are few studies demonstrating the CASP effect with other antifungal agents. In most cases, the combination therapy of CASP with another agent is used for treating infections caused by the genus Candida [ 22 , 23 ]. In association with farnesol, CASP significantly inhibited the metabolic activity of Candida parapsilosis cells [ 24 ].…”
Section: Introductionmentioning
confidence: 99%